CALCULATION OF THE BUDGET PLAN FOR THE CONSTRUCTION OF THE BULAK GOMBAL, BANTUL REGENCY - Dangga Loma, Verawati Kartika; Sari, Sely Novita; Maulana, Rizal (ReTII, 2022)
The meeting hall is a multipurpose building that is usually used for various activities such as meetings and deliberation where people can express their aspirations for the common good. The meeting hall building which is planned for Bulak Gombal Hamlet is 150m2 in size, the construction of building spaces is more focused on large rooms for activities with many participants. This meeting hall can also be used as a means of increasing the economy by making the meeting hall a batik center for mothers.The research method used in this study is a descriptive research method, namely by directly interviewing the parties concerned and also data obtained from direct observations in the field. Several literature studies were also conducted by utilizing a more in-depth analysis which was realized by more focused and comprehensive data processing. Based on the analysis of the budget plan carried out, it can be concluded that the cost needed to build the Meeting Hall in Bulak.